Intracellular signaling pathways of inflammation modulated by dietary flavonoids: The most recent evidence. Issue 17 (22nd November 2018) - Chen, Lei; Teng, Hui; Jia, Zhen; Battino, Maurizio; Miron, Anca; Yu, Zhiling; Cao, Hui; Xiao, Jianbo
ABSTRACT: Dietary flavonoids, which occur in many plant foods, are considered as the most active constituents among the plant-derived ones in vitro and in vivo . To date, many studies have addressed the anti-inflammatory activity of flavonoids. However, their considerable structural diversity and in vivo bioavailability make them able to modulate different signaling pathways. The present review attempted to summarize and highlight a broad range of inflammation-associated signaling pathways modulated by flavonoids. Finally, based on the current scientist's literature, structure-activity relationships were concluded. Dietary flavonoids have the ability to attenuate inflammation by targeting different intracellular signaling pathways triggered by NF-κB, AP-1, PPAR, Nrf2, and MAPKs. Identification of the main structural features required for the modulation of these inflammation-related pathways (hydroxylation pattern, C2=C3 double bond) have an important role to play in the development of new anti-inflammatory drugs.